2021
DOI: 10.1111/jcmm.16577
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical cord‐derived MSC and hyperbaric oxygen therapy effectively protected the brain in rat after acute intracerebral haemorrhage

Abstract: This study tested the hypothesis that combined therapy with human umbilical cord‐derived mesenchymal stem cells (HUCDMSCs) and hyperbaric oxygen (HBO) was superior to either one on preserving neurological function and reducing brain haemorrhagic volume (BHV) in rat after acute intracerebral haemorrhage (ICH) induced by intracranial injection of collagenase. Adult male SD rats (n = 30) were equally divided into group 1 (sham‐operated control), group 2 (ICH), group 3 (ICH +HUCDMSCs/1.2 × 106 cells/intravenous in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
(97 reference statements)
1
8
0
Order By: Relevance
“…An essential finding in the present study was that the inflammation and circulation and oxidative stress biomarkers in the brain tissue were found to be substantially increased, followed by remarkably increased in the apoptotic, fibrotic, DNA-damaged and mitochondrial damage biomarkers in hemorrhagic brain tissues. In this way, our findings, in addition to corroborating with the findings of the previous studies [ 25 27 , 30 , 31 , 33 , 34 ], could, at least in part, explain why the BHV was markedly increased in ICH animals. Paramount importance was that these molecular-cellular perturbations were notably reversed by one dose and more notably reversed by two consecutive doses of cell therapy.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…An essential finding in the present study was that the inflammation and circulation and oxidative stress biomarkers in the brain tissue were found to be substantially increased, followed by remarkably increased in the apoptotic, fibrotic, DNA-damaged and mitochondrial damage biomarkers in hemorrhagic brain tissues. In this way, our findings, in addition to corroborating with the findings of the previous studies [ 25 27 , 30 , 31 , 33 , 34 ], could, at least in part, explain why the BHV was markedly increased in ICH animals. Paramount importance was that these molecular-cellular perturbations were notably reversed by one dose and more notably reversed by two consecutive doses of cell therapy.…”
Section: Discussionsupporting
confidence: 92%
“…Numerous studies have revealed that tissue/organ in circumstances of ischemia and necrosis always drew forth of large amount of inflammation and oxidative stress, which in turn, stimulated cell stress signaling, resulting in DNA/mitochondrial damage and cell apoptosis and death [ 25 27 , 30 , 31 , 33 , 34 ]. An essential finding in the present study was that the inflammation and circulation and oxidative stress biomarkers in the brain tissue were found to be substantially increased, followed by remarkably increased in the apoptotic, fibrotic, DNA-damaged and mitochondrial damage biomarkers in hemorrhagic brain tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abundant data have shown that mesenchymal stem cells (MSCs) therapy effectively protected the organs from different disease entities mainly through inhibiting the inflammation and innate and adaptive immunity through down-regulating immunogenicity [ 32 37 ]. Our recent phase I clinical trial also demonstrated that human umbilical cord-derived mesenchymal stem cells (HUCDMSCs) therapy was safe and life-saving for moderate–severe acute respiratory distress syndrome (ARDS) patients [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recently published study that combined umbilical cord-derived MSCs with hyperbaric oxygen to treat ICH in mice reported that combined treatment was significantly better than a single treatment [ 77 ]. Although they believe that this is inseparable from the low immunogenicity of hUC-MSCs and the effects of hyperbaric oxygen therapy on improving MSCs levels, the specific molecular mechanism remains to be elucidated [ 110 , 111 ]. WJ-derived mesenchymal stromal/stem cells (WJ-MSCs) are hUC-MSCs with primitive stemness properties.…”
Section: Stem Cells Sources For Ich Treatmentmentioning
confidence: 99%